2015
DOI: 10.1159/000442821
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Decreases Thyroid Volume and Nodule Size in Subjects with Insulin Resistance: A Preliminary Study

Abstract: Objective: The aim of this study was to investigate the effects of metformin on thyroid volume and nodule size. Subjects and Methods: Prospective data were gathered on 100 newly diagnosed subjects with insulin resistance (68 female, 32 male) between August 2008 and May 2010. Each subject followed a standard diet and exercise program, and received 1,700 mg/day of metformin therapy for 6 months. The height, weight, waist circumference (WC) and thyroid hormone levels of each subject were measured. Additionally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 18 publications
1
34
0
6
Order By: Relevance
“…Recently, a preliminary study also found that metformin therapy significantly decreased thyroid volume and nodule size in subjects with IR (Anil et al 2016). Therefore, in patients with IR and nodular goiter, metformin may be a useful drug both to decrease IR and the size of solid nodules.…”
Section: :1mentioning
confidence: 96%
“…Recently, a preliminary study also found that metformin therapy significantly decreased thyroid volume and nodule size in subjects with IR (Anil et al 2016). Therefore, in patients with IR and nodular goiter, metformin may be a useful drug both to decrease IR and the size of solid nodules.…”
Section: :1mentioning
confidence: 96%
“…Experimental studies have shown that metformin via activation of AMP-kinase and mTOR (mammalian target of rapamycin) exhibits inhibitory effects on the growth of thyroid cells and antagonises the pro-growth effect of insulin [47]. In the population of patients with insulin resistance, metformin therapy resulted in a reduction in volume of thyroid and nodules [48]. In addition, Ittermann et al showed that type 2 diabetes patients treated with metformin have a lower thyroid volume compared to those treated with other hypoglycaemic agents [49].…”
Section: Goitre and Thyroid Cancermentioning
confidence: 99%
“…Badania eksperymentalne wykazały, że metformina poprzez aktywację AMP-kinazy i szlaku mTOR (mammalian target of rapamycin) wykazuje właściwości hamujące na wzrost komórek tarczycy i antagonizuje pro-wzrostowy efekt insuliny [47]. W populacji osób z insulinoopornością terapia metforminą PRACE POGLĄDOWE powodowała zmniejszenie wola i objętości guzków tarczycy [48]. Ponadto, Ittermann i wsp.…”
Section: Prace Poglądoweunclassified
“…Treatment with metformin has been shown to reduce insulin resistance and has been associated with a decrease in thyroid nodule size [3,4]. In a 6-months study of 66 women with insulin resistance and NTD, metformin therapy was associated with a 30% median reduction in nodule size while the combination of levothyroxine and metformin was associated with 55% reduction [10].…”
Section: Discussionmentioning
confidence: 99%
“…While there are no studies linking exogenous insulin treatment in T2DM and thyroid nodule growth, there is mounting evidence that insulin resistance and endogenous hyperinsulinaemia are associated with nodule development [2] and that reduction of insulin resistance has favourable effects on nodule size [3,4]. Hyperinsulinaemia may also be associated with an increased risk of differentiated thyroid carcinoma [5] and persistence of disease post-operatively [6].…”
Section: Introductionmentioning
confidence: 99%